Діяльність органів управління місцями ув’язнення на місцях в умовах реалізації тюремної реформи Павла Скоропадського - Гламазда, П.; Glamazda, P. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті висвітлено проблеми реалізації тюремної реформи в Українській Державі в період перебування при владі гетьмана Павла Скоропадського. Охарактеризовано органи управління місцями ув’язнення на місцях, проаналізовано штатний розпис та посадові оклади для персоналу губернських інспекцій та персоналу тюремних закладів, відповідно до їх категорій. Проаналізовано питання кадрового забезпечення губернських інспекцій та пенітенціарних установ. This article presents problems of the penal reform realization in Ukraine in a period when hetman Skoropadskyi held the reins of power. The Activities of State Government Bodies over penal institutions on place have been described; a mane schedule and an official salary for the regional inspection’s staff and staff for custodial facility have been analyzed according to their categories. Staffing issues have been analyzed in the regional inspections and penitentiaries. It has been determined that the prison administration and the regional prison inspectorate followed by the legal framework which was still in the period of the Russian Empire.
Activities of Custodial Management on the Ground in Terms of Prison Reform Implementation by Pavlo Skoropadskii
Keywords: Українська Держава; гетьманат; пенітенціарна система; губернська тюремна інспекція; тюремна установа; Ukrainian State; Hetmanate; the penitentiary system; the provincial prison inspection; prison facility